2020
DOI: 10.1111/wrr.12883
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of three different multilayer dressings for pressure ulcer prevention on sacral skin after prolonged loading: An exploratory crossover trial

Abstract: Evidence suggests that preventive dressings applied on sacral skin help to prevent pressure ulcers. However, possible performance differences of different dressing types are unclear. An exploratory randomized crossover trial with intra‐individual comparisons was conducted to compare the effects of three different multi‐layer foam dressings (Mepilex Border Sacrum, ALLEVYN Life Sacrum and Optifoam Gentle Sacrum) compared to no dressing on the sacral skin. Healthy female volunteers (n = 12, mean age 72 years) wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 38 publications
(131 reference statements)
4
22
0
Order By: Relevance
“…In addition, comparing baseline with post loading values indicates that 2 hours loading on a basic foam mattress leads to an increase of skin temperature, TEWL, SCH, epidermal hydration, and erythema 30 . Similar observations were described previously and indicate that mechanical loading of heel and sacral skin on a basic foam mattress leads to occlusion and to a variety of structural skin and soft tissue changes 9‐11,35,36 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, comparing baseline with post loading values indicates that 2 hours loading on a basic foam mattress leads to an increase of skin temperature, TEWL, SCH, epidermal hydration, and erythema 30 . Similar observations were described previously and indicate that mechanical loading of heel and sacral skin on a basic foam mattress leads to occlusion and to a variety of structural skin and soft tissue changes 9‐11,35,36 …”
Section: Discussionsupporting
confidence: 74%
“… 30 Similar observations were described previously and indicate that mechanical loading of heel and sacral skin on a basic foam mattress leads to occlusion and to a variety of structural skin and soft tissue changes. 9 , 10 , 11 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…There seemed to be an increase of IL-1α after loading at the sacrum. This is supported by a recent study by Wert et al 16 who showed reduced IL-1α releases during mechanical stimulation when wearing a dressing compared with no dressing. Interestingly, median differences between baseline and post-loading at the heels and sacrum were higher in group A compared with group C, indicating a possible protective effect of the dressing during loading.…”
Section: Discussionsupporting
confidence: 70%
“…For example, Wert et al 15 investigated the inflammatory response of the skin in healthy participants after combined loading of pressure and shear applied on the volar aspect of both forearms in the absence or presence of three foam dressings. Lechner et al 16 suggest that there are differences regarding the cutaneous response between wearing a dressing and no dressing during loading and that there seem to be differences between different dressings. However, neither the heel skin nor the effects of wearing dressings without loading were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation